2007
DOI: 10.1002/jqs.1081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of δ13C and C/N ratios in bulk organic matter as palaeosalinity indicators in Holocene and Lateglacial isolation basin sediments, northwest Scotland

Abstract: 2007. Assessment of 13 C and C/N ratios in bulk organic matter as palaeosalinity indicators in Holocene and Lateglacial isolation basin sediments, northwest Scotland.ABSTRACT: Carbon isotopes (d 13 C) and C/N ratios from bulk organic matter have recently been used as alternative proxies for relative sea-level (RSL) reconstruction where there are problems associated with conventional biological indictors. A previous study on a single isolation basin (Upper Loch nan Eala) in northwest Scotland has shown a clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The potential of sediment δ 13 C values as salinity proxy was already suggested by Hedenström and Possnert, 2001 [96], and further explored by e.g. Mackie et al [101,102]. The salinity changes observed in zones 3 to 4 are suggested to show increased marine influence in the western part of the Limfjord (through the western opening of the fjord towards the North Sea), whereas the northern http://www.heritagesciencejournal.com/content/1/1/24 openings diminished as a result of isostatic uplift, aeolian sand transport and redeposition of sediment by ocean currents, mainly the Jutland Current.…”
Section: Sediment Core Samples From the Limfjordmentioning
confidence: 85%
“…The potential of sediment δ 13 C values as salinity proxy was already suggested by Hedenström and Possnert, 2001 [96], and further explored by e.g. Mackie et al [101,102]. The salinity changes observed in zones 3 to 4 are suggested to show increased marine influence in the western part of the Limfjord (through the western opening of the fjord towards the North Sea), whereas the northern http://www.heritagesciencejournal.com/content/1/1/24 openings diminished as a result of isostatic uplift, aeolian sand transport and redeposition of sediment by ocean currents, mainly the Jutland Current.…”
Section: Sediment Core Samples From the Limfjordmentioning
confidence: 85%
“…In Unit 2, C/N values were greater than 20, indicating predominantly sustained allochthonous, terrestrial organic input (Meyers and Teranes 2001). The C/N vs. δ 13 C biplot also supported this interpretation, with values plotting within the C3 plant range (Meyers and Lallier-Vergés 1999;Mackie et al 2007). …”
Section: Bulk Sediment Geochemistrymentioning
confidence: 60%
“…The C/N values (between 10 and 20) indicated that both terrestrial and aquatic carbon sources contributed to lake sedimentation (Meyers and Teranes 2001); however, the C/N vs. δ 13 C biplot (Fig. 4) indicated that the aquatic carbon likely had a strong freshwater affinity (Mackie et al 2007). The Cl concentrations were low and indicated that saltwater egress did not occur during this interval (Branchu and Bergonzini 2004).…”
Section: Bulk Sediment Geochemistrymentioning
confidence: 99%
“…Lagoon isolation has been inferred for Norwegian (Mills et al 2009;Balascio et al 2011) and Scottish (Mackie et al 2005;Mackie et al 2007) basins, which transformed into freshwater coastal lakes as a result of isostacy or land uplift. However, natural forcing is unlikely since Irish coasts, with the exception of a small portion of Northern Ireland, are submergent (Gehrels 2010).…”
Section: Chronologymentioning
confidence: 97%
“…C/N ratios of c. 9 have been attributed to benthic algal communities in shallow water sediments (Sundbäck et al 2000). Algae and macrophytes have a wide range of d 15 N (Finaly and Kendall 2007) and values of c. 2 at the base of LM2 core are possibly representative of phytoplankton (Maksymowska et al 2000;Rossi et al 2010). Basal core diatom records have relatively high concentrations (9.00 ) 10 5 frustules g (1 WW), are mainly composed of benthic species and assemblages comprising marine and brackish taxa, including high levels of Paralia sulcata.…”
Section: Chronologymentioning
confidence: 99%